"A Day in My life" Photography Project: The Silent Voice of Pediatric Bone Marrow Transplant Patients. (September 2014) - Breitwieser, Carrie L.; Vaughn, Lisa M.
A photovoice project was conducted with pediatric bone marrow transplant (BMT) patients to examine their coping skills and interpretation of their experience during a BMT, especially when hospitalized. We also wanted to determine how photovoice could be used within a pediatric BMT unit. Sixteen children (ages 4-14) and 2 young adults (ages 22 and 25) from a pediatric BMT unit participated in the project. Six BMT outpatients participated in the data analysis and evaluation phase. Fourteen clinical staff evaluated the impact of the project on their practice. Three primary themes emerged from the pre- and post-BMT photos, accompanying detailed notes, and BMT outpatient analysis of the photos: ( a ) BMT is "torture, " ( b ) BMT is "time slipping away, " and ( c ) BMT requires normalization, comfort, distraction, and support. BMT patients and staff concluded that photovoice helped express and release emotions regarding the challenges of BMT. BMT staff noted that the results of this project reminded them of the importance of being patient-centered and mindful of patient experience and the therapeutic relationship.